A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam. Issue 9 (3rd May 2022) - Yu, Yi-Fan; Li, Yue-Qian; Wang, Ru-Yue; Liu, Xu; Cui, Wen-Bo; Chen, Xiao-Han; Zhao, Cheng-Mu; Qi, Feng-Ming; Zhang, Zhan-Xin; Fei, Dong-Qing
Abstract: A new highly oxygenated germacranolide, carcerlane A (1 ), together with four known highly oxygenated germacranolides (2 –5 ), was isolated from an ethanol extract of the whole plant of Carpesium nepalense var. lanatum (C.B.Clarke) Kitam. The structures were determined by HRESIMS and extensive analysis of their spectroscopic data including IR, 1 D and 2 D NMR spectra. To our best knowledge, it was the first time to report the phytochemical investigation on this plant. The anti-Alzheimer's disease (AD) activities of 1 –5 were evaluated using Caenorhabditis elegans AD pathological model. All the tested compounds showed that they have the anti-AD bioactivities of delaying worms paralysis. Graphical Abstract: